The Impact of Digital Marketing on Consumer Involvement in Zambia during the Covid-19 Epidemic - Katongo, Bwalya; Musawa, Nsama (International Journal of Scientific Research and Management (IJSRM), 2022)
Digital marketing is the promotion of products and services using the internet and digital technologies such as computers, mobile phones, websites and social media platforms. Digital marketing has been increasingly popular in recent years. Due to restrictions in travelling during the Covid-19 pandemic people spent more time online than before a situation that caused digital marketing become a key tool in the hands of brands and marketers. Customer behavior had evolved and technology had advanced due to the above. The purpose of the descriptive study was to evaluate the influence of digital marketing on consumer involvement in Zambia during the Covid-19 pandemic. SMEs and group administrators for social media groups involved in online marketing, selling and buying of products were among the most common respondents. The study found that during the pandemic there was an increase in digital marketing and online business activities, indicating a positive impact on consumer participation in digital marketing and that cultural practice had no bearing on customers’ decisions to buy things online.KEYWORDS: Covid19, Digital Marketing, Online buying, selling, consumer involvement